Essentials of mass communication theory - Berger, Arthur Asa, 1933- (Thousand Oaks : Sage Publications, 1995)
This book takes the student step-by-step through the key theories in each area of mass communication including text, audience, media and production. An ideal text for undergraduate courses.
Making sense of mass communication -- The artwork (or text) -- Media -- The audience -- America/society -- The artist.
Includes bibliographical references (pages 192-196) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Mass media -- Philosophy; Mass media -- United States; Médias -- Philosophie; Médias -- États-Unis.; SOCIAL SCIENCE -- Media Studies; Mass media; Mass media -- Philosophy; United States; Massenkommunikation; Theorie; Massacommunicatie; Communicatietheorie; Mass media; United States